Long-term effects and user acceptance of back-support exoskeletons in the workplace - Julia Riemer; Sascha Wischniewski (Zeitschrift für Arbeitswissenschaft, 2023)
The aim of our study was to evaluate the long-term effects of back-support exoskeletons (BSEs) in occupational settings. Valuable insights were gained through repeated in-depth interviews with occupational safety professionals over a~one-year period regarding the use and impact of BSEs over a~one-year period. The results highlight a~significant lack of user acceptance, primarily due to movement restrictions and discomfort. Passive BSEs (PassEXOs) were reported to be sometimes uncomfortable, restricting mobility and causing pressure point discomfort, while quasipassive soft BSEs (SoftEXO) received more positive feedback. In addition, factors such as proper fit, adjustability, hygiene maintenance, and the ease of donning and doffing were identified as key determinants of employee acceptance of BSEs. By gaining a~deeper understanding of these factors, organisations can facilitate a~successful and sustainable integration of BSE technology into the workplace.
Keywords: 650; Safety specialists; Periodic interviews; Field study; Subjective evaluation; Factors influencing use